(untitled) (Basel, Switzerland, 2000)
It is a compilation of recent advances in the understanding of these proteins' structures, mechanisms of action, and their biological roles and functions. In addition, the book contains sections devoted to the mechanisms of folding and to addressing the molecular physiology and pathology of these families of proteins, which are of intense biomedical interest. Emerging information regarding the participation of these proteins in enzymatic activity and their significance in biotechnology applications, such as the use of specific inhibitors, is also included. The topics treated comprise genetic regulation, evolutionary and cell biological aspects, as well as the latest information on structures and mechanisms operating in these proteins.
Keywords: Vitamin B6,PQQ ( biochemistry ),Enzymes; Congresses,Congresses,Regulation,Congresses